Comparative Behavior of Viscose-Based Supercapacitor Electrodes Activated by KOH, H2O, and CO2 - Stefan Breitenbach; Jiri Duchoslav; Andrei Ionut Mardare; Christoph Unterweger; David Stifter; Achim Walter Hassel; Christian Fürst (Nanomaterials, 2022)
Activated carbons derived from viscose fibers were prepared using potassium hydroxide, carbon dioxide, or water vapor as activation agents. The produced activated carbon fibers were analyzed via scanning electron microscopy and energy dispersive X-ray spectroscopy, and their porosity (specific surface area, total pore volume, and pore size distribution) was calculated employing physisorption experiments. Activated carbon fibers with a specific surface area of more than 2500 m2 g−1 were obtained by each of the three methods. Afterwards, the suitability of these materials as electrodes for electrochemical double-layer capacitors (supercapacitors) was investigated using cyclic voltammetry, galvanostatic measurements, and electrochemical impedance spectroscopy. By combining CO2 and H2O activation, activated carbon fibers of high purity and excellent electrochemical performance could be obtained. A specific capacitance per electrode of up to 180 F g−1 was found. In addition, an energy density per double-layer capacitor of 42 W h kg−1 was achieved. These results demonstrate the outstanding electrochemical properties of viscose-based activated carbon fibers for use as electrode materials in energy storage devices such as supercapacitors.